The Influence Of Price, Promotion and Marketing Event On Customers’ Repurchasing Decision Of Flashy Products - Yusuf, Ramayani; Hendrayati, Heny; Veranita, Mira; Agustina, Granit; Pramanik, Nuniek Dewi (Universitas Muhammadiyah Sidoarjo, 2021)
This research aims to investigate the influence of prices, promotions and marketing events on the customers’ repurchasing decision of Flashy products. The survey was conducted to 221 customers of Flashy Women's Clothing Bandung which is a brand of women's clothing from the age of 15-45 years. The data used for this research was collected through questionnaires distributed to the students of Polytechnic Piksi Ganesha who have had shopping experience in Flashy. This study used a structural equation model (SEM) to evaluate the suitability of the theoretical model being analyzed related to empirical data, and to test the significance of the hypothesis. The results showed that the estimated coefficient of standardized regression in which price, promotion and event marketing have a significant influence on customer’s repurchase decisions.